Rancang Bangun Aplikasi Pengenalan Cerita Rakyat Timun Mas Berbasis Game 3D - Kholid Fathoni; Jauari Akhmad Nur Hasim; Muhammad Zakky Fathony; Rizky Yuniar Hakkun; Rengga Asmara (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2018)
Indonesia is a country that has diverse cultures such as folklore. At this time many folklore is increasingly forgotten especially by the younger generation, one of them is Timun Mas. This raises concerns about the extinction of Timun Mas folklore as Indonesia's cultural heritage. The cause of the younger generation to forget the folklore is due to unattractive packaging, as well as the entry of various games that come from outside which can also carry the content of foreign cultures. Therefore required a media that can pack the folklore so interesting to learn by the younger generation. The author gives an idea how to package the folklore of Timun Mas so interesting by using 3D gaming technology as an alternative of learning media. Folklore of Timun Mas is visualized in the game as interesting characters, appropriate gaming environment, and supported graphics and audio capabilities are sufficient. By using 3D games technology, users can play games that contain learning so that users will not feel bored. The results of this experimental study show that Timun Mas game can run on desktop devices, all 3D characters can be implemented properly. From the results of user surveys also shows that this game can serve as a learning medium, easy to use and has an attractive appearance.